Oral Exam, or About the Specifics of Taking Exams in Modern Research Universities - O. V. Mikhailov (Высшее образование в России, 2018)
The article presents the author’s considerations regarding two different forms of examinations for students of higher education institutions, both oral and written. The author expresses the view that the crucial argument for deciding which of the two possible forms, oral or written, should be used is the possibility to identify such student knowledge that is not related to any other ways of obtaining information from outside. While using the written form of examination in modern conditions (all-round access to Internet, smartphones) it is impossible to verify how a student treats and applies the knowledge as there is no personal contact between the student and an examiner. The examiner cannot ask him questions for further clarification. The author argues that at present the only acceptable form for assessing such knowledge is an oral examination.